Il luogo del lavoro domestico in discussione: letture giuridiche femministe - Lerussi, Romina Carla (2014)
In Argentina, domestic work is not part of labor regulations made by the Labor Agreement Law (law 20.744/1976) but it is controlled by a special statute. As main objective of this special regulation, it has been taken into account its specifications also know as notes or defining legal elements of this job: workplace (at home or particular houses), its orientation (familiar life) and finally the lack of profits and/or the direct economical benefit. In this article, we have carried out a theoretical-conceptual, juridical and feminist analysis of the first note, the workplace (home or particular houses), through a legal approach of juridical speeches produced in Argentina.